Prenatal diagnosis of a giant placental choriocarcinoma with favorable maternal and fetal outcomes: A case report and literature review. - Mmari, Elisha; Timoth, Editha (Ethiopian Journal of Reproductive Health, 2026)
Abstract Introduction Placental chorioangioma is a benign tumor from chorionic tissue, usually in the third trimester. It’s the most common placental tumor, but prevalence is unclear since many are small and asymptomatic. Large tumors (>5 cm) are rare but linked to severe maternal and fetal issues like anemia, hydrops, and polyhydramnios. Diagnosis uses ultrasound, Doppler, and MRI. Management varies from monitoring to procedures like laser ablation or amnioreduction. Case presentation A 22-year-old woman at 36 weeks pregnant was referred after a routine ultrasound detected a placental mass. She had no symptoms, normal vital signs, and fetal movements. The ultrasound showed a 6.5×7.5 cm vascular placental lesion consistent with chorioangioma, along with polyhydramnios. During conservative management, the tumor enlarged, causing severe polyhydramnios, fetal distress, and Doppler evidence of fetal anemia. An urgent cesarean was performed, revealing an 11×10 cm chorioangioma. The neonate was admitted to NICU, confirmed anemia, and needed a blood transfusion. Histopathology verified a benign chorioangioma, and both mother and baby were discharged in good condition. Conclusion Placental chorioangioma, especially giant forms, links to high perinatal complications and poor maternal-fetal outcomes. Prenatal assessments via ultrasound and color Doppler are essential for early diagnosis and management. However, limited resources in low- and middle-income countries hinder timely detection and treatment, increasing risks for mother and baby.